Numerical Analysis for Heat Transfer Augmentation in a Circular Tube Heat Exchanger Using a Triangular Perforated Y-Shaped Insert - Lokesh Pandey; Satyendra Singh (Fluids, 2021)
The present investigation constitutes CFD analysis of the heat transmission phenomenon in a tube heat exchanger with a Y-shaped insert with triangular perforation. The analysis is accomplished by considering air as a working fluid with a Reynolds number ranging from 3000 to 21,000. The segment considered for analysis consists of a circular tube of 68 mm diameter and 1.5 m length. The geometrical parameter considered is the perforation index (0%, 10%, 20%, and 30%). The constant heat flux is provided at the tube wall and a pressure-based solver is used for the solution. The studies are performed for analyzing the effects of inserts on the heat transfer and friction factor in the circular tube heat exchanger which results in augmented heat transfer at a higher perforation index (PI) and lower friction factor. The investigation results show that the highest heat transfer is 5.84 times over a simple plain tube and the maximum thermal performance factor (TPF) is 3.25 at PI = 30%, Re = 3000.